PEMBUATAN SEDIAAN TEH CELUP DAUN SALAM (Syzygium polyanthum) DENGAN PENAMBAHAN RIMPANG JAHE MERAH (Zingiber officinale Rosc. Var. Rubrum) UNTUK KESEHATAN - Septiwi, Rizki Eka; Ratnasari, Dewi; Handayani, Reti Puji (Sekolah Tinggi Ilmu Kesehatan Holistik, 2019)
Objective: This study aims to make a preparation of tea bags of bay leaves (Syzygium polyanthum) with the rhizome of red ginger (Zingiber officinale Rosc. Var. Rubrum) to reduce uric acid levels easy and is practically consumed by the public. Methods: This research uses action research method to use research instrument in the form of interview sheet, observation sheet and questionnaire test preferences. Dosage is made by comparison between the composition of leaves : red ginger (to 2.5:1, 2,5:1,5 and 2,5:2). Results: The result showed shrinkage of drying of bay leaves as much as 3.2% and ginger red 5% this is in accordance with the requirements of the crude drug i.e. a water content of less than 10%. Viewed in organoleptic dosage tea bag leaves resistant and stable during 3 weeks of storage with the proportions of the formula the most preferred respondents is a formula 3 with the addition of red ginger as much as 2 grams is 96,67%. Conclusion: The Preparation of tea bag favored by the public, namely the formula of the third with the addition of red ginger 2 grams and the dosage is stable in storage for 3 weeks at room temperature.